Lehninger Principles of Biochemistry - Nelson, David Lee Cox, Michael M (W.H. Freeman And Company, 2005)
New edition of what is often considered the single best text on biochemistry, focusing on communicating to students the fundamentals of biochemistry in a way that reflects the field as it is understood today. Major recent advances covered range from the draft sequence of the human genome to elucidation of the high-resolution structure of the ribosome.